RFX2 Is a Major Transcriptional Regulator of Spermiogenesis. - W Stephen Kistler; Dominique Baas; Sylvain Lemeille; Marie Paschaki; Queralt Seguin-Estevez; Emmanuèle Barras; Wenli Ma; Jean-Luc Duteyrat; Laurette Morlé; Bénédicte Durand; Walter Reith (PLoS Genetics, 2015)
Spermatogenesis consists broadly of three phases: proliferation of diploid germ cells, meiosis, and finally extensive differentiation of the haploid cells into effective delivery vehicles for the paternal genome. Despite detailed characterization of many haploid developmental steps leading to sperm, only fragmentary information exists on the control of gene expression underlying these processes. Here we report that the RFX2 transcription factor is a master regulator of genes required for the haploid phase. A targeted mutation of Rfx2 was created in mice. Rfx2-/- mice are perfectly viable but show complete male sterility. Spermatogenesis appears to progress unperturbed through meiosis. However, haploid cells undergo a complete arrest in spermatid development just prior to spermatid elongation. Arrested cells show altered Golgi apparatus organization, leading to a deficit in the generation of a spreading acrosomal cap from proacrosomal vesicles. Arrested cells ultimately merge to form giant multinucleated cells released to the epididymis. Spermatids also completely fail to form the flagellar axoneme. RNA-Seq analysis and ChIP-Seq analysis identified 139 genes directly controlled by RFX2 during spermiogenesis. Gene ontology analysis revealed that genes required for cilium function are specifically enriched in down- and upregulated genes showing that RFX2 allows precise temporal expression of ciliary genes. Several genes required for cell adhesion and cytoskeleton remodeling are also downregulated. Comparison of RFX2-regulated genes with those controlled by other major transcriptional regulators of spermiogenesis showed that each controls independent gene sets. Altogether, these observations show that RFX2 plays a major and specific function in spermiogenesis.